Implementation of Care Management: An Analysis of Recent AHRQ Research. (February 2018) - Tomoaia-Cotisel, Andrada; Farrell, Timothy W.; Solberg, Leif I.; Berry, Carolyn A.; Calman, Neil S.; Cronholm, Peter F.; Donahue, Katrina E.; Driscoll, David L.; Hauser, Diane; McAllister, Jeanne W.; Mehta, Sanjeev N.; Reid, Robert J.; et al.
Care management (CM) is a promising team-based, patient-centered approach "designed to assist patients and their support systems in managing medical conditions more effectively." As little is known about its implementation, this article describes CM implementation and associated lessons from 12 Agency for Healthcare Research and Quality–sponsored projects. Two rounds of data collection resulted in project-specific narratives that were analyzed using an iterative approach analogous to framework analysis. Informants also participated as coauthors. Variation emerged across practices and over time regarding CM services provided, personnel delivering these services, target populations, and setting(s). Successful implementation was characterized by resource availability (both monetary and nonmonetary), identifying as well as training employees with the right technical expertise and interpersonal skills, and embedding CM within practices. Our findings facilitate future context-specific implementation of CM within medical homes. They also inform the development of medical home recognition programs that anticipate and allow for contextual variation.